Can Metabolic Syndrome Presence Predict Carotid Intima-Media Thickness? - Timóteo, AT (2012)
The aim of this investigation was to analyze metabolic syndrome (MS) impact on carotid intima-media thickness (cIMT). Prospective study of 300 patients with suspected coronary artery disease admitted for an elective coronary angiography were evaluated. Patients with previously known cardiac disease were excluded. In the population, 23.0% were diabetics and 40.5% had MS (but no diabetes). cIMT was not significantly different in patients with MS, but was significantly higher in diabetic patients compared with MS and control patients. Independent predictors of cIMT were age, male gender, insulin, and high-density lipoprotein (HDL) cholesterol (the last one with an inverse association). In patients without MS, only age and HDL cholesterol were associated. In patients with MS, independent predictors were age, male gender, and glucose, and abdominal obesity showed an inverse relationship. In patients with stable angina, MS is not an independent predictor of cIMT. Nonmodifiable variables (age and gender) are the most important determinants of cIMT, as well as blood glucose, in MS patients. Abdominal obesity was protective. J Clin Hypertens (Greenwich). 2012;00:00-00. ©2012 Wiley Periodicals, Inc.